Jordan : Supporting Stable Development in a Challenging Region, A Joint World Bank-Islamic Development Bank Evaluation - Hassan, Fareed M. A.; Al-Saci, Djelloul (Washington, DC: World Bank, 2013)
This evaluation, prepared in collaboration with the Islamic Development Bank, looks at the effectiveness of Bank assistance to Jordan during the 1990s, from three perspectives: an analysis of the Bank's services and products, development impact, and the contribution of the Bank and its development partners, to development outcomes. The Bank's strategy since 1990, based on wide-ranging and influential analytic and advisory activities, was to support macroeconomic stabilization and pro-market structural reforms to foster growth. The increased focus on the social sectors was aligned with the Millennium Development Goals (MDGs). The strategy was relevant to the government's priorities outlined in a series of five-year economic and social development plans. The Bank's programs, in particular, were successful in promoting policy reforms. Substantial tariff, trade and financial sector reforms, together with the removal of disincentives for investment and the privatization of government enterprises, were achieved. Bank assistance also contributed to significant progress in the agriculture, water and social sectors. With Bank support, Jordan made excellent progress in almost all areas covered by the MDGs, and is likely to meet the target levels by 2015. However, these gains have been achieved in an inefficient manner and the cost in terms of public expenditures has been relatively high. Recommendations outline much needed public sector reform, for despite some public expenditures being curtailed, the country's vulnerability to external shocks, remains high, and the potential for regional instability is also considerable. Future Bank assistance should focus on public expenditure restructuring, enhanced water management and conservation, and poverty reduction.